International Electron Devices Meeting 1991 [Technical Digest]
DOI: 10.1109/iedm.1991.235321
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effect of dynamic stressing on high-field endurance and stability of reoxidized-nitrided, fluorinated and conventional oxides

Abstract: Absbuct-Highfield endurance of reolddiud-oitrided oxide @NU), and fluorinated oxide (pox) under dynamic Fowkr-Nordheln strm were compared with that of conventional oxide. Timedependent dielectric breakdown (TDDB) of RNU and FOX is & o m to be strongly dependent on frequency, m d lifetime under high frequency stress is longer relative to that under DC stress. RNU and FOX display interface hardness under high field iojection at all frequencies.hterface trap generation is not a stroog function of frequency in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We confirmed that, for example, the durations for which the voltages exceed 10V are at most 0.3ns. Therefore it may be inferred that the gate oxides won't be damaged in the early stage of discharge [11].…”
Section: Voltages Across the Gate Oxides In The Early Stage Of Dischargementioning
confidence: 99%
“…We confirmed that, for example, the durations for which the voltages exceed 10V are at most 0.3ns. Therefore it may be inferred that the gate oxides won't be damaged in the early stage of discharge [11].…”
Section: Voltages Across the Gate Oxides In The Early Stage Of Dischargementioning
confidence: 99%
“…It has been shown that hole trapping is correlated with oxide breakdown [4]. A hole trapping/migration model has been proposed to explain the increased lifetime under high-frequency stress observed for reoxidized ",-nitrided oxides [3]. According to this model, there exist two competing mechanisms: first, the hole trapping rate which will decrease with frequency due to detrapping by tunneling, and second, the drift distance of the trapped hole from the anode which will also decrease with frequency.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…One of the reasons for G, degradation is the increase in Dit which leads to channel mobility decrease [3]. To examine ADit as a function of frequency, the chargepumping technique is used and AZcpmax, the increase in the maximum charge-pumping current as 5 is varied, is plotted in Fig.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that, for example, the durations for which the voltages exceed 10 V are at most 0.2 ns. Therefore it may be inferred that the gate oxides in the input buffer won't be damaged in the early stage of discharge [11].…”
Section: Voltages Across the Gate Oxides In The Early Stage Of Dischargementioning
confidence: 99%